Relaxation-compensated CEST (chemical exchange saturation transfer) imaging in breast cancer diagnostics at 7T - Loi, Lisa; Zimmermann, Ferdinand; Görke, Steffen; Korzowski, Andreas; Meißner, Jan-Eric; Deike-Hofmann, Katerina; Stieber, Anne; Bachert, Peter; Ladd, Mark E.; Schlemmer, Heinz-Peter; Bickelhaupt, Sebastian; Schott, Sarah; et al. (European journal of radiology, 2020)
Purpose - To investigate whether fat-corrected and relaxation-compensated amide proton transfer (APT) and guanidyl CEST-MRI enables the detection of signal intensity differences between breast tumors and normal-appearing fibroglandular tissue in patients with newly-diagnosed breast cancer. - Method - Ten patients with newly-diagnosed breast cancer and seven healthy volunteers were included in this prospective IRB-approved study. CEST-MRI was performed on a 7T-whole-body scanner followed by a multi-Lorentzian fit analysis. APT and guanidyl CEST signal intensities were quantified in the tumor and in healthy fibroglandular tissue after correction of B0/B1-field inhomogeneities, fat signal contribution, T1- and T2-relaxation; signal intensity differences of APT and guanidyl resonances were compared using Mann-Whitney-U-tests. Pearson correlations between tumor CEST signal intensities and the proliferation index Ki-67 were performed. - Results - APT CEST signal in tumor tissue (6.70±1.38%Hz) was increased compared to normal-appearing fibroglandular tissue of patients (3.56±0.54%Hz, p=0.001) and healthy volunteers (3.70±0.68%Hz, p=0.001). Further, a moderate positive correlation was found between the APT signal and the proliferation index Ki-67 (R2=0.367, r=0.606, p=0.11). Guanidyl CEST signal was also increased in tumor tissue (5.24±1.85%Hz) compared to patients’ (2.42±0.45%Hz, p=0.006) and volunteers’ (2.36±0.54%Hz, p<0.001) normal-appearing fibroglandular tissue and a positive correlation with the Ki-67 level was observed (R2=0.365, r=0.604, p=0.11). APT and guanidyl CEST signal in normal-appearing fibroglandular tissue was not different between patients and healthy volunteers (p=0.88; p=0.93). - Conclusion - Relaxation-compensated and fat-corrected CEST-MRI allowed a non-invasive differentiation of breast cancer and normal-appearing breast tissue. Thus, this approach represents a contrast agent-free method that may help to increase diagnostic accuracy in MR-mammography.
Gesehen am 13.08.2020